Development of DH-AODV routing protocol for wireless mesh networks - Zainab Senan Mahmod (Kulliyyah of Engineering, International Islamic University Malaysia, 2010)
Wireless mesh networks (WMNs) have emerged as a key technology for nextgeneration wireless networking. Although WMNs can be built up based on existing technologies, field trials and experiments with existing WMNs prove that the performance of WMNs is still far below expectations. Therefore, several challenging research issues need to be resolved. One of the most effective factors to improve the performance of WMNs is the routing protocol used. There are many performance issues need to be improved such as robustness, QoS, security, power consumption, and scalability which is the most critical issue in WMNs. Current researches are trying to develop new protocols or enhance some of the Ad-hoc protocol to be adapted to WMNs. This research aims to design and implement a routing protocol that improves the scalability of the WMNs. To achieve this, a Directional Hierarchical Ad-hoc On Demand Vector (DH-AODV) routing protocol is proposed. The DH-AODV is taking advantage of the existing fields in the AODV's control packets in order to reduce the load on the network's bandwidth and to quickly detect route breakage. The proposed protocol is designed, implemented and evaluated using Qualnet Simulator. The Adhoc on Demand Distance Vector (AODV) is selected as a benchmark. Simulation results indicate that this enhanced routing protocol can 47% reduce the end-to-end delay of data packets, improve the throughput by 11.2%, and decrease the packet loss rate 20% less than the standard AODV.